2009
DOI: 10.1038/labinvest.2009.47
|View full text |Cite
|
Sign up to set email alerts
|

Non-histone nuclear factor HMGB1 is phosphorylated and secreted in colon cancers

Abstract: The high mobility group box 1 (HMGB1) protein, a non-histone nuclear factor, is overexpressed and localizes to the cytoplasm in some cancer cells. However, the mechanism of cytoplasmic HMGB1 transport, extracellular secretion, and its role in cancer progression is not clear. To simulate the activated state of HMGB1, we mutated serine residues of nuclear localization signals (NLSs) to glutamic acid and performed transfection assays. We carried out a kinase inhibitor study and evaluated the cell migration by inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 37 publications
3
71
1
1
Order By: Relevance
“…And it is safe to say that post translational modifications play an important role in the nucleocytoplasmic redistribution. As mentioned above, oxidation, hyperacetylation and phosphorylation of HMGB1 contribute to its cytoplasmic relocation in inflammatory and cancer cells (Hoppe et al, 2006;Youn et al, 2006;Tsung et al, 2007;Kang et al, 2009;Evankovich et al, 2010;Lee et al, 2012). Experiments in Schistosoma mansoni conclusively demonstrated that acetylation and phosphorylation played roles in cellular trafficking, culminating with its secretion to the extracellular milieu de Abreu da Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…And it is safe to say that post translational modifications play an important role in the nucleocytoplasmic redistribution. As mentioned above, oxidation, hyperacetylation and phosphorylation of HMGB1 contribute to its cytoplasmic relocation in inflammatory and cancer cells (Hoppe et al, 2006;Youn et al, 2006;Tsung et al, 2007;Kang et al, 2009;Evankovich et al, 2010;Lee et al, 2012). Experiments in Schistosoma mansoni conclusively demonstrated that acetylation and phosphorylation played roles in cellular trafficking, culminating with its secretion to the extracellular milieu de Abreu da Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…Later, it has been demonstrated that decreased histone deacetylases(HDACs) activity in hepatocytes, following ischemia and reperfusion, was a mechanism that promoted hyperacetylation and secretion of HMGB1 (Evankovich et al, 2010). In addition, several investigations demonstrated that HMGB1with phosphorylation at specific serine residues of nuclear localization signals (NLS) regions was transported to cytoplasm, and subsequently secreted from cells (Youn et al, 2006;Kang et al, 2009;Lee et al, 2012). Hence, it is safe to say that post translational modifications (PTMs) play a critical role in governing the nucleocytoplasmic shuttling of HMGB1.…”
Section: Introductionmentioning
confidence: 99%
“…HMGB1 is a nuclear protein that acts as a chromatin-binding factor and exists in the nuclei of cancerous and normal cells (17). HMGB1 modifies the interaction of DNA with transcription factors, including p53 steroid hormone receptors, by non-specifically binding to the minor groove of DNA, thereby playing a role in DNA repair, transcription, differentiation, extracellular signalization, and somatic recombination (39).…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 demonstrates affinity for various DNA structures, including supercoiled and single-stranded DNA, B-and Z-DNA, DNA mini-circles, 4-way junctions, looped structures, hemicatenated DNA, and triplex DNA (39). Native HMGB1 released from tumor cells inhibits DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…DNA'nın küçük oluğuna nonspesifik şekilde bağlanarak p53, steroid hormon reseptörleri de dahil olmak üzere bazı transkripsiyon faktörleri-nin DNA ile etkileşimini modifiye eder. DNA onarımında, transkripsiyonda, diferansiasyonda, extraselüler sinyalizasyonda, somatik rekombinasyonda rol oynar [2]. Bu nükleer fonksiyonları-nın yanı sıra nekroze hücrelerden pasif, inflamasyonda rol oynayan hücrelerden aktif sekrete edilerek ekstraselüler sinyal molekülü olarak da fonksiyon görür.…”
Section: Introductionunclassified